(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2025)
The disciplinary code of history (Cuesta Fernández, 1997), defined by the ideas, discourses and practices in school teaching, has privileged the study of the hegemonic male subject. This androcentrism, entrenched in the history taught, begins to be questioned gradually and increasingly, among other factors, given the entry of the gender category as an explanatory variable. As a hypothesis, we propose how this gendered disciplinary code of history (XXXX, 2023) has been reconfigured, in recent decades, promoting other ideas and practices that advocate polyphony and intersectionality. To do this, three sections are displayed. The first reflects on the history researched and taught in terms of gender and takes up previous research where I investigated the city of La Plata, Province of Buenos Aires. The following sections place the analysis in another jurisdiction and take, as a case study, the recently implemented secondary school Curriculum Design (CD) of the province of Neuquén. There, the document itself and the voices of key informants interviewed who participated in the curriculum construction process are contemplated and it is explored: how the gender category enters the CD, in the knowledge of History in particular and the training in gender is problematized.